Exploring Sustainable Culinary Tourism Practices in Nganggring Tourism Village, Yogyakarta - Witara, I Made; Larasati, Sri; Karmin, Enny (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2025)
Nganggring Tourism Village is one of the advanced tourism villages in Sleman Regency, with significant potential for implementing sustainable culinary tourism. This study aims to explore environmentally friendly culinary tourism practices by integrating a sustainability perspective. This research employs a qualitative approach with a case study method. The study was conducted in Nganggring Hamlet, Girikerto, Turi, Sleman, from September to November 2024. The research subjects include the Head of the Independent Livestock Farmers Group of Nganggring, the Head of the Independent Farmers Cooperative of Nganggring, the Women’s Empowerment Group (PKK) of Girikerto Hamlet, and the Nganggring Tourism Village Management. Data collection techniques involve observation, interviews, and documentation. The research findings reveal that Nganggring Tourism Village possesses natural, cultural, and artificial tourism potentials, including the processing of salak pondoh (snake fruit), jemparingan (traditional archery), and Etawa goat farming. Sustainability practices are implemented through local resource management, waste reduction, the use of local ingredients in culinary offerings, and the promotion of salak-based cuisine and Etawa goat milk products. These initiatives add value by balancing economic benefits with environmental conservation. This study is expected to serve as a reference model for other tourism villages in Indonesia seeking to adopt sustainable culinary tourism practices.